Faculty Attitudes Towards Open Access Publishing, E-Print Servers and Institutional Repositories - Wust, Markus (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This qualitative study investigates how faculty gather information for teaching and research and their opinions on open access approaches to scholarly communication. Despite generally favorable reactions, a perceived lack of peer review and impact factors were among the most common reasons for not publishing through open-access forums. Cette étude qualitative examine comment les membres du corps professoral recueillent l’information pour l’enseignement et la recherche, et leurs opinions envers les approches de la communication scientifique à libre accès. Malgré des réactions généralement favorables, le manque perçu de révision par les pairs et les facteurs d’impact comptent parmi les motifs habituellement évoqués pour ne pas publier sur ces tribunes à libre accès.